تأثير معدل التبريد على الخواص الميكانيكية للخام الصلب الثنائي الطور - احمد رجب, مصطفى; فالح حسن, احمد (Journal of Engineering and Sustainable Development, 2010)
The results of this research work showed that the increase of the cooling rate will increase the amount of martensite that will reduce the weldability of the dual phase steel. The low percentage carbon enables water to be as a suitable quenching medium for production of the dual phase steel of better weldability than the quenching medium of a salt solution The results also showed that the increased annealing time causes growth of the austenite grain size without affecting its amount. Annealing for a period of more than 10 minutes produces a structure of polygonized ferrite-martensite, while annealing for 10 minutes or less the structure will be polygonized ferrite – pearlaite with small amount of martensite. Bearing in mind that the weldability depends on the amount of the martensite phase its distribution within matrix.